Pengaruh Model Team Games Tournament Terhadap Hasil Pembelajaran Bahasa Indonesia di Sekolah Dasar - Romansur, Jahra Malika; Darrmawati, Desak Made (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the effect of Indonesian language learning outcomes using the Team Games Tournament (TGT) learning model on fifth-grade students of SDN Ciracas 06 Pagi semester 2 of the 2023/2024 academic year. The research method used is a quantitative research method with a quasi-experimental design research design using a non-equivalent posttest-only control group design. The determination of the control class and experimental class in the study was carried out by comparing their daily learning values. They are using multiple choice instruments with a total of 25 questions. Furthermore, the analysis of the required data tests was carried out namely, the normality test using the Liliefors test, while the homogeneity test used the Fisher test. In the hypothesis test used the t-test obtained t count 2.005 and t table 0.679 α = 0.05 then H0 is rejected which states that there is an effect on Indonesian language learning outcomes using the Team Games Tournament (TGT) learning model on fifth-grade students at Ciracas 06 Jakarta Elementary School.